Strategi Pemasaran Digital Produk Scarlett Whitening dalam Meningkatkan Penjualan - Armiani, Fandrisly; Akmalia, Putri; Mahardika, Rama; Permana, Erwin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Scarlett Whitening is a phenomenon. This product, which was just released in 2018, led the care product market in August 2021 on Shopee and Tokopedia, with the largest market share of 18.9%. The use of digital technology is the main factor driving the popularity of Scarlett Whitening products. Even though in general the business world today cannot be separated from digitalization, the success of Scarlet Whitening has been spectacular. The research was conducted with a qualitative descriptive approach. The data comes from observations of Scarlett Whitening's live streaming, as well as secondary data support obtained through searches on various popular official sites. The results showed that the strategy used by Scarlett Whitening in marketing and increasing sales was by utilizing social media. The strategy undertaken includes increasing the number of influencers in promoting their products within a certain time according to the agreement with Brand Ambassadors, such as Artists, Celebgrams, and models. Keywords: digital marketing, sales, beauty products, scarlett whitening.